Being different : more Neoplatonism after Derrida - Gersh, Stephen. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2013)
Having now benefited from viable editions and studies of many of the most important authors within the Neoplatonic tradition of western philosophy, it is time for us to read these materials more actively in terms of the philosophical developments of the late twentieth century that provide the greatest opportunities for intertextual exploration. The hermeneutical project that beckons was begun in Stephen Gersh's Neoplatonism after Derrida: Parallelograms (Brill, 2006) and is raised to a higher power in his present volume. Here a new course is charted in the reading of such ancient authors as Proclus, Damascius, Augustine, Pseudo-Dionysius, and Meister Eckhart through a critical engagement with the deconstructions of pagan and Christian Neoplatonic texts in the writings of Jacques Derrida.